Calculus II For Dummies, 2nd Edition - Zegarelli (For Dummies, 2012)
An easy-to-understand primer on advanced calculus topics Calculus II is a prerequisite for many popular college majors, including pre-med, engineering, and physics. Calculus II For Dummies offers expert instruction, advice, and tips to help second semester calculus students get a handle on the subject and ace their exams. It covers intermediate calculus topics in plain English, featuring in-depth coverage of integration, including substitution, integration techniques and when to use them, approximate integration, and improper integrals. This hands-on guide also covers sequences and series, with introductions to multivariable calculus, differential equations, and numerical analysis. Best of all, it includes practical exercises designed to simplify and enhance understanding of this complex subject. Introduction to integration Indefinite integrals Intermediate Integration topics Infinite series Advanced topics Practice exercises Confounded by curves? Perplexed by polynomials? This plain-English guide to Calculus II will set you straight!